(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The investigations are related to the development of the methods of total water demand estimation for the crops cultivated in the irrigated conditions of different agricultural zones. The agro-climatic indicators recorded in 2015–2019 by 10 hydrometeorological stations served as baseline data. The maximum crops water demand per decades has been calculated via CropWAT software. The soil moisture monitoring results enable to disclose the effect of various evapotranspirations on the moisture dynamics in the soil. The changing pattern of the crops total evaporation speed at different values of soil depth has been disclosed, while based on the mathematical processing of the experimental results, a calculated formula has been derived, which enables to solve the problem of crops coefficient calculation in non-standard conditions. The new mathematical model for the detection of moisture change in the soil, depicts the soil moisture regime more precisely, which enables to describe the dynamics of total evaporation from the soil and plant surfaces for the period of irrigation intervals in more precise manners.